Peningkatan Hasil Belajar IPAS Materi Membangun Masyarakat yang Beradab melalui Model Problem Based Learning Berbantuan Media Kartu Bergambar pada Peserta Didik Kelas IVA SDN Sampangan 02 Semarang - M Sukron; Barokah Isdaryanti; Hayuk Dining Tyastuti (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this study is to determine the increase in science learning activities and outcomes through the Problem Based Learning model assisted by picture cards in class IVA students of SDN Sampangan 02 Semarang. The type of research used is collaborative classroom action research (PTK) with a qualitative approach. There are four stages of collaborative classroom action research, namely 1) planning, 2) implementation, 3) observation, and 4) reflection. The subjects of this study are students of class IVA SDN Sampangan 02 Semarang in semester 2 of the 2022/2023 academic year. Data collection techniques include observation, tests, and interviews. The instruments used in this study were multiple-choice questions with the help of the quiziz website, observation sheets of student learning activities, and interviews of initial science skills. The KKTP for science subjects determined by the school is 75. The results showed that there has been an increase in activity and learning outcomes from precycle to cycle 1 and to cycle 2. Evidenced by the increase in student learning activities from pre-cycle with an average percentage of 49% to cycle I with an average percentage of 75% and to cycle II with an average percentage of 85.5% in learning. The learning outcomes of students in the pre-cycle obtained an average score of 68.9 with classical completeness of 46% with very less qualifications. The improvement in learning outcomes is evidenced by an evaluation test conducted at the end of the first cycle, the results of science learning showed an average grade score of 78.6 with classical completeness of 71% with sufficient qualifications. In cycle II the grade point average increased to 81.8 with classical completeness of 86% in good qualifications. The increase occurred in student learning activities from the percentage obtained from 46% to 75% and to 85.5% with very good criteria. Thus, it can be concluded that the application of the Problem Based Learning model assisted by picture cards can improve the learning outcomes and learning activities of students in science subjects in class IVA SDN Sampangan 02 Semarang.